ANALISIS KOMPARASI PROMOSI SOSIAL MEDIA DAN REVIEW PRODUK PADA MARKETPLACE TOKOPEDIA DAN LAZADA TERHADAP KEPUTUSAN PEMBELIAN - Achmad arief Firmansyah (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2023)
Along with rampant e-commerce competition in Indonesia, Tokopedia and Lazada are among the top four e-commerce companies that dominate the online shopping market in Indonesia. Tokopedia is one of the largest digital-based companies in Indonesia. Founded on February 6, 2009 by William Tanuwijaya and Leontinus Alpha Edison under the auspices of PT. Tokopedia. Lazada Group operates websites in Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam. Lazada Indonesia itself was founded in 2012 and is operating until now. For PT. Lazada Indonesia is the official Lazada Group branch in Indonesia. There is a disparity in the number of visits to the two marketplaces. This study uses quantitative methods with survey research using a questionnaire as an instrument. The population in this study were male and female users of online shopping applications and had made purchases in the Tokopedia and Lazada marketplaces. The data analysis technique used to answer the hypothesis is the independent t test. The results of this study showed a significance of 0.045 <0.05. Which means that there is a significant difference in the Product Review variable on purchasing decisions at Tokopedia and Lazada. It can be concluded that this shows that there are differences in product reviews by consumers at Tokopedia and Lazada.